The Impact of Green Organizational Culture on Employee Performance: A Field Study on Jeddah Municipality Employees in Makka Al-Mukarramah Region - Al Qir, Abdulaziz; Jifri, Ali (The Arab Journal of Administration, 2023)
The study aimed to identify the impact of green organizational culture on the employee performance of Jeddah Municipality workers in Makkah. This study gained its theoretical significance as it deals with the importance of green employee performance and the green organizational culture, while it is considered of a practical importance as it provides recommendations and research proposals to develop the green practices and green employee performance. The study relied on the descriptive approach as the study method and used the questionnaire as the study tool. The study community consisted of all employees working in the Jeddah Municipality and the study sample included (200) workers. The study concluded that there was a statistically significant positive correlation between the depth of greening the organizational culture on the employee performance of Jeddah Municipality workers in Makkah Province with (.801**) at the level of significance of (.000), there was a statistically significant positive correlation between the degree of greening the organizational culture on the employee performance of Jeddah Municipality workers in Makkah with (.817**) at the level of significance of (.000), and that there was a statistically significant positive correlation between spreading the greening of the organizational culture on the employee performance of Jeddah Municipality workers in Makkah with (.831**) at a level of significance of (.000). The study recommended the importance of forming a partnership with the private sector in order to develop investments towards green sectors and working on developing financial and economic procedures and mechanisms in line with the implementation of the Green Culture Program.